Effectiveness of Aspiration Under Ultrasound Guidance in Breast Abscess in Terms of Early Resumption of Breast Feeding: A Randomized Controlled Trial - Akif Amin, Rang Ali, Atif Iqbal, Javaid Sajjad Hashmi, Imtiaz Ahmed Khattak, Haider Kamran (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Effectiveness of aspiration under ultrasound guidance in breast abscess in terms of early resumption of breast feeding. Study Design: Randomized controlled trial Place and Duration: Mardan Medical Complex and Teaching Hospital and Jinnah International Hospital, Abbottabad, from November, 2021 to April, 2022. Methods: There were a total of 140 female participants. The patients ranged in age from 16 to 50. After obtaining the patient’s written consent, demographic information including age, weight, height, and body mass index were collected. Breast abscess diagnosed on clinical examination and ultrasound breast were included. Seventy patients were assigned to Group I and treated with percutaneous aspiration, whereas the same number were assigned to Group II and underwent incision drainage. Early breast feeding was restored in both groups and compared for their respective outcomes. The entire dataset was analyzed using SPSS 20.0. Results: We observed that the percentage of patients in group I who were able to resume breast feeding was 61 (87.1%), and in group II was found in 42 (60%) patients. The level of comfort experienced by patients in group I 60 (85.7%), as compared to group II 35 (50%), was significantly greater. Conclusion: In this study, we came to the conclusion that percutaneous aspiration in breast abscess was successful and effective in comparison to incision drainage, with less problems and a high percentage of satisfaction among the women. Keywords: Incision drainage, Breast abscess, Percutaneous aspiration